2012
DOI: 10.1002/ardp.201100448
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Human Monoamine Oxidase Inhibitory Activities of Some 3,5‐Diaryl‐N‐substituted‐4,5‐dihydro‐1H‐pyrazole‐1‐carbothioamide Derivatives

Abstract: Sixteen 3-aryl-5-(4-fluorophenyl)-N-substituted-4,5-dihydro-1H-pyrazole-1-carbothioamide derivatives were synthesized and their structure were identified by UV, IR, (1) H NMR, mass spectra, and microanalyses. The compounds were evaluated in vitro for their human monoamine oxidase (hMAO) inhibitory activities and their MAO-A and -B selectivity. All the compounds were found to potently inhibit MAO-A isoforms. 5-(4-Fluorophenyl)-3-(4-methoxyphenyl)-N-methyl-4,5-dihydro-1H-pyrazole-1-carbothioamide (1.0 × 10(-3)  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…1 H-NMR: δ 3.10 (1H, dd, H A ), 3.18 (3H, s, NH-CH 3 ), 3.78 (1H, dd, H B ), 6.02 (1H, dd, H X ) (J AB : 17.6, J AX : 4.0, J BX : 12.0 Hz), 7.08-7.73 (8H, m, aromatic prot. 3-(4-Fluorophenyl)-5-(4-methylphenyl)-N-methyl-4,5dihydro-1 H -pyrazole-1-carbothioamide (11) Yield: 45.8 %, mp 149 °C. IR (cm − 1 ): 3 362 (N-H), 1 602 (C = N), 1 348 (C 4 -H), 1 320 (C = S), 1 004 (C 5 -N 1 ).…”
Section: -(4-mentioning
confidence: 99%
See 1 more Smart Citation
“…1 H-NMR: δ 3.10 (1H, dd, H A ), 3.18 (3H, s, NH-CH 3 ), 3.78 (1H, dd, H B ), 6.02 (1H, dd, H X ) (J AB : 17.6, J AX : 4.0, J BX : 12.0 Hz), 7.08-7.73 (8H, m, aromatic prot. 3-(4-Fluorophenyl)-5-(4-methylphenyl)-N-methyl-4,5dihydro-1 H -pyrazole-1-carbothioamide (11) Yield: 45.8 %, mp 149 °C. IR (cm − 1 ): 3 362 (N-H), 1 602 (C = N), 1 348 (C 4 -H), 1 320 (C = S), 1 004 (C 5 -N 1 ).…”
Section: -(4-mentioning
confidence: 99%
“…The docking study was performed by using MOE software to understand the orientations of the most active ligand in MAO-A enzyme. The S enantiomer of 9 was preferred for docking studies according to our previous study [ 11 ] . In the binding pose with the lowest energy, it was observed that the 4-Cl phenyl ring at C5 of pyrazole located into the hydrophobic pocket formed by Tyr 444, Tyr 407 and FAD.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Successively, sixteen new 3-aryl-5-(4-fluorophenyl)-Nsubstituted-4,5-dihydro-1H-pyrazole-1-carbothioamide derivatives were synthesized and their structure were fully characterized as reported in Fig. ( 17) [43]. The compounds were evaluated in vitro for their human monoamine oxidase inhibitory activities and selectivity.…”
Section: Pyrazoline Derivatives As Potent Mao Inhibitorsmentioning
confidence: 99%